Methods to identify protein targets of metal-based drugs. (April 2023) - Skos, Lukas; Borutzki, Yasmin; Gerner, Christopher; Meier-Menches, Samuel M.
Abstract: Metal-based anticancer agents occupy a distinct chemical space due to their particular coordination geometry and reactivity. Despite the initial DNA-targeting paradigm for this class of compounds, it is now clear that they can also be tuned to target proteins in cells, depending on the metal and ligand scaffold. Since metallodrug discovery is dominated by phenotypic screenings, tailored proteomics strategies were crucial to identify and validate protein targets of several investigative and clinically advanced metal-based drugs. Here, such experimental approaches are discussed, which showed that metallodrugs based on ruthenium, gold, rhenium and even platinum, can selectively and specifically target proteins with clear-cut down-stream effects. Target identification strategies are expected to support significantly the mechanism-driven clinical translation of metal-based drugs.